ECONOMIC AND MATHEMATICAL MODELING OF OPTIMAL CHOICE OF INVESTMENT PROJECTS ON RAILWAY TRANSPORT WITH RISK ACCOUNTING - Kudrytska, N. V. (Science and Transport Progress, 2007)
There are the considered existent indexes and methods of estimation of efficiency of investment projects in the article. First offered economic-mathematical model of the nonlinear programming of choice of optimum investment projects taking into account the risk and basic factors which influence on profitability.